2014
DOI: 10.1111/j.1728-4465.2014.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

Demand for Contraception to Delay First Pregnancy among Young Married Women in India

Abstract: In India, evidence is sparse regarding the demand for contraception to delay first pregnancy among married young people. Using data drawn from a study conducted in six Indian states among 9,572 women aged 15-24 who were married for five or fewer years, we explore the scope of this demand, the extent to which it has been satisfied, and, using logistic regression analyses, the factors correlated with contraceptive use to delay first pregnancy among those reporting demand. Findings confirm considerable demand for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 18 publications
3
70
0
Order By: Relevance
“…For the present study based in rural India, inequitable power dynamics between husbands and wives is common. Recent research from India shows that men husbands are decision-makers and often have control over family planning, especially among rural young couples (IIPS, 2007; Jejeebhoy, Santhya, & Zavier, 2014; Stephenson & Tsui, 2002). Child marriage is relatively common and young wives tend to have husbands who exercise even greater control over family planning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the present study based in rural India, inequitable power dynamics between husbands and wives is common. Recent research from India shows that men husbands are decision-makers and often have control over family planning, especially among rural young couples (IIPS, 2007; Jejeebhoy, Santhya, & Zavier, 2014; Stephenson & Tsui, 2002). Child marriage is relatively common and young wives tend to have husbands who exercise even greater control over family planning.…”
Section: Introductionmentioning
confidence: 99%
“…Child marriage is relatively common and young wives tend to have husbands who exercise even greater control over family planning. Also, in rural areas, low levels of contraceptive knowledge and of marital communication and negotiation make contraceptive use difficult for women even if they would like to limit childbearing (Jejeebhoy, Santhya, and Zavier 2014).…”
mentioning
confidence: 99%
“…A recent study carried out in five states of India has, however, revealed that there is substantial demand for contraception among young married women to postpone their first pregnancy, but only a small proportion of these women use any contraception [19]. It is, however, not clear, how much of the unmet need of contraception among young married women is due to the lack of resolve to practice contraception and how much of the unmet need is due to supply side factors.…”
Section: Journal Of Contraceptive Studies Issn 2471-9749mentioning
confidence: 99%
“…But factors such as lack of awareness of sexual and reproductive matters, lack of knowledge about appropriate contraceptive methods, limited spousal communication and family pressure prevented women to practice contraception (Jejeebhoy et al , 2014). Younger newly married women in our country initiate use of any family planning method only after they have had at least one child or after completing the desired family size.…”
Section: Contraceptive Use and Differentialsmentioning
confidence: 99%